(untitled) (Journal of Comparative & International Higher Education, 2022)
We explore how the influx of foreign funding into the higher education sectors of the United States and United Kingdom has raised the challenge of “reputation laundering”—when foreign donors and individuals use donations to prestigious universities to boost their international public image and offset negative images or reported controversies back in their home country. We outline four pathways for reputation laundering—donations for academic programs/schools, naming rights, honorary degrees and board seats; and the offer of favorable admissions decisions—and examine the variety of policies, practices and safeguards that have been adopted by U.K. and U.S. universities in response. We present evidence, drawn from a survey of U.K. development officers, that university diligence procedures, which usually focus on compliance with the law, often are inadequate for filtering or deterring most types of reputation laundering.